Nonlinear optical properties of two-dimensional palladium ditelluride (PdTe2) and its application as aerosol jet printed saturable absorbers for broadband ultrafast photonics. (March 2022) - Cheng, Ping Kwong; Ahmed, Safayet; Qiao, Junpeng; Wong, Lok Wing; Yuen, Chun Fai; Saleque, Ahmed Mortuza; Ivan, Md. Nahian Al Subri; Hani, Sumaiya Umme; Hossain, Mohammad Ismail; Zhao, Jiong; Wen, Qiao; Tsang, Yuen Hong
Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDs) have recently gathered substantial interest in the advanced photonic field due to their strong broadband absorption, tunable bandgap, and excellent nonlinear optical (NLO) properties. Palladium ditelluride (PdTe2 ) is a novel TMD material with high carrier mobility, great stability, and narrow bandgap, allowing it to be used in a wide range of applications such as superconductors, phototransistors, and millimeter-wave receivers. Here, the NLO properties of PdTe2 are investigated by Z-scan technology. The highest nonlinear absorption coefficient of PdTe2 has been determined as -9.25 × 10 3 cm/GW (1 µm) and -0.55 × 10 3 cm/GW (1.5 µm), implying its admirable NLO characteristics. Subsequently, for the first time, broadband PdTe2 -based saturable absorbers (SAs) are prepared by utilizing the aerosol jet printing (AJP) method. By employing this PdTe2 based SA, the generation of broadband ultrafast laser pulses from the near-to-mid-infrared regime with pulse durations in the ps to fs range (170 ps, 570 fs, and 1.59 ps in 1 μm, 1.5 μm, and 2 μm laser sources, respectively) further signify the capability of PdTe2 as an ideal NLO material for ultrafast photonics devices. Moreover, Q-switched and high-repetition-rate (0.7 GHz) based 58 th harmonic mode-locked pulses in the telecommunication band are also obtained with this SA. These findings indicate that 2D-PdTe2 is a promising material for nonlinear optics and broadband ultrafast photonics applications. Graphical abstract: Image, graphical abstract